The Effectiveness of Flipped Learning in Teaching Writing - Gusti Nyoman Ayu Sukerti; Elina Rudiastari; Kadek Yogi Susana (Soshum: Jurnal Sosial dan Humaniora, 2020)
ABSTRACT ___________________________________________________________________ Flipped learning provides an opportunity for students to use most of the time in class to focus on the discussion process and group work so that students gain experience deep and autonomous learning. This study was conducted to determine the effectiveness and impact of implementing flipped learning which includes academic aspects. There were twenty-five four students took part as the object of this study. This study involved delivering material in the learning process for one semester divided into two types of instruction, namely the format of traditional face-to-face lectures and flipped learning in two cycles. Quantitative data were obtained from the results of pre-tests and essays written by students before and after the implementation of the action in the form of the application of flipped learning teaching methods. The results of the pre-test and post-test assessment were analyzed using the SPSS statistical program 21 to analyze the effect of flipped learning on improving student learning achievement. This classroom action research was conducted in two cycles in which the quantitative data, i.e., three set of data including (pre-test and post-test1), (pre-test and post-test2) and (post-test1 and post-test2) were analyzed using SPSS statistic 21. The finding showed that the correlation coefficient (r) of the first data set was 0,856, the second data set was 0,778 and the third data set was 0,889. Based on the interpretation scale of correlation coefficient by Guilford (1965), the range of all the correlation coefficients implies that there is a strong relationship between before and after the treatment of PBL. Based on the result of analysis using SPSS statistics 21 with 95% level of confidence, it was revealed that -tcount < -ttable (-9,007 < -2,06390, -14,105 <-2,06390 and -9,789<-2,06390) for all data set and the significance value of 2-tailed was less than 0,05 (0,000 < 0,05). It can be concluded that H1 was accepted and H0 was rejected signifying that there was a significant effect of flipped learning implementation in improving students’ writing achievement.